FORECASTING THE PROSPECTIVE VOLUME OF CARGO TRANSPORTATION FOR THE DEVELOPMENT OF THE TRANSPORT NETWORK - Kuziyev, Abdimurot (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The content of the article is mainly concerned with solving the problem of efficient distribution of cargo flows in the transport network and their optimal development in accordance with the growth (dynamics) of traffic volumes, taking into account the throughput of the road. For this, methods for generating initial data and determining their reliability are presented. As an example, predictive calculations of an increase in the volume of cargo transportation in the Surkhandarya region were performed using the time series method and an analysis was presented.